PENGETAHUAN MENGENAI PERUNDUNGAN PADA GURU DI JAKARTA DITINJAU DARI JENJANG MENGAJAR - Novendawati Wahyu Sitasari; Wara Rahmawati; Yuli Asmi Rozali; Noni Agustina (Universitas Narotama, 2021)
Bullying has become an international problem and usually occurs in the school environment. Bullying behavior in children can be significantly reduced thanks to the cooperation of the community, counselors, teachers and students. Teacher commitment is a decisive factor in reducing bullying cases. Most teachers have not responded to bullying incidents effectively and tend to ignore them. One of the reasons for the lack of handling done by the teacher is the teacher's low knowledge of bullying behavior. The purpose of this study was to determine knowledge about teacher bullying in Jakarta in terms of teaching levels. This study used a comparative design involving 64 teachers of kindergarten, elementary, junior high and high school in Jakarta and its surroundings. The measuring instrument used is based on references from Olweus (1993) and the Teacher Inventory of Skills and Knowledge (TISK) compiled by Horne, Bartolomucci, & Newman (2004). Data analysis using ANOVA and the results obtained were no differences in knowledge about bullying in terms of teaching level (F = 0.512, p> 0.05). Then based on the distribution of data, it can be seen that many teachers who teach at the elementary level have high knowledge of bullying. More female teachers have high knowledge of bullying than male teachers. The higher the age, the more knowledgeable about bullying is low. Keywords: Knowledge, Bullying, Teacher